A Review of Nepalese Buddhism in Rural Development: Evidence from the Himalayan Buddhist Belt - Shrestha, Kiran (Research Nepal Journal of Development Studies, 2024)
Nepalese Buddhism has historically influenced rural development, particularly in the Himalayan belt, where monastic institutions, religious values, and community practices intersect with socio-economic initiatives. This review synthesizes the historical evolution, doctrinal foundations, and thematic roles of Buddhism in rural development across Himalayan communities, including Solukhumbu, Mustang, and Dolpo. Using a mixed chronological and thematic literature review methodology, it examines Buddhist contributions to social capital, education, local economies, community-based tourism, gender equity, and environmental stewardship. Real case studies highlight monastic-led development programs and indigenous practices. The review identifies gaps in longitudinal research, interdisciplinary studies, and policy integration, offering directions for sustainable rural development strategies informed by Buddhist principles.